Early Film Cultures in Taiwan, Hong Kong, and Republican China Kaleidoscopic Histories - Yeh, Emilie Yueh-yu (University of Michigan Press, 2018)
This collection explores the complex world of early cinema in China, Hong Kong, and Taiwan. The story of how cinema established itself in China has not been well-understood. Cultural models for cinema-going and industry practices varied widely across China. By looking at several centers of cinematic activity, going beyond commercial fiction film to include non-fiction films (such as educational film), and taking on Cantonese as well as Mandarin productions. Beyond the Silver Screens presents early cinema in China in a new light Highlights Hong Kong, Taipei and Guangzhou as well as better-know examples from Shanghai, these essays foreground the cinema's relationships with imperialism and colonialism, examining how cinematic culture established itself by adapting to distinctive local social and artistic practices, emphasizing the potency of cinema as a sociocultural institution.